Political parties in the Russian Federation: object or subject of public control? - Goncharov, Vitaly V. (Journal of the Belarusian State University. Law, 2022)
This article is devoted to the analysis of the place and role of political parties in the organisation and functioning of the institute of public control in Russia. The purpose of the research is to substantiate the solution of the legal dilemma as to whether political parties in the Russian Federation are an object or a subject of public control. The object of the research is public relations associated with the organisation and functioning of the institute of public control in Russia. The subject of the research is the norms of Russian legislation governing the participation of political parties in the organisation and functioning of the institute of public control. The article analyses the influence of political parties on the processes of organisation and functioning of the institute of public control in the Russian Federation. The author substantiates the position that political parties act as objects of public control, since the main goal of their activities is to participate in the processes of organising and exercising public power in the country; they are endowed with electoral legislation with the rights of nominating their candidates for various elective positions in public authorities; they receive budgetary funding in Russia; state and municipal employees in the Russian Federation, as a rule, are the members of one or another political party; in the country during the reign of President V. V. Putin, there is a lack of equal conditions for participation in the election processes of political parties, coupled with the dominance of one political party («United Russia»); political parties can be classified as organisations endowed with separate public powers.
Keywords: political parties; the Russian Federation; public control; civil society; object; subject; democracy; constitutional principles; globalisation; elections